The Application of Gamification Method to Enhance Students’ Learning Motivation in Vocational English Classes - Syahidallah, Syahidallah; Karomi, Karomi; Saputra, Ari (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of the gamification method in enhancing students’ learning motivation in vocational education. Gamification integrates game elements such as points, badges, leaderboards, and rewards into the learning process to foster engagement and motivation. The research applied a qualitative case study approach involving an English teacher and ten 12th-grade students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that gamification positively influenced students’ motivation, with significant improvements in participation, enthusiasm, collaboration, and perseverance during class activities. Students reported that learning became more enjoyable, interactive, and less monotonous, while teachers observed higher confidence and engagement among previously passive learners. The transformation of motivation from extrinsic—driven by rewards—to intrinsic—driven by self-satisfaction and curiosity—was also evident. In conclusion, gamification effectively increased students’ motivation and created a more student-centered learning environment, although limited facilities and preparation time remained challenges for broader implementation.